2016
DOI: 10.1007/s12265-016-9704-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload or Oxidative Stress? Insight into a Mechanism of Early Cardiac Manifestations of Asymptomatic Hereditary Hemochromatosis Subjects with C282Y Homozygosity

Abstract: Hereditary hemochromatosis (HH) is a genetic disorder which affects the heart due to systemic iron overload and concomitant elevated oxidative stress. Increasing numbers of patients are diagnosed at an asymptomatic stage due to genetic testing. Subclinical abnormal left ventricular diastolic function (LVDF) and increased arrhythmias are noted in this population; however, the mechanism leading to these observances has not been well understood. In this study, we assessed the relationship between arrhythmia activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Iron is a strong prooxidant transition element. Due to this feature, it can cause cellular damage in different tis sues by generating reactive oxygen species [24,37]. Another possible mechanism could be based on Hevi et al's research [38].…”
Section: T a B L E 1 B -Distribution Of Parameters Between Gendersmentioning
confidence: 99%
“…Iron is a strong prooxidant transition element. Due to this feature, it can cause cellular damage in different tis sues by generating reactive oxygen species [24,37]. Another possible mechanism could be based on Hevi et al's research [38].…”
Section: T a B L E 1 B -Distribution Of Parameters Between Gendersmentioning
confidence: 99%
“…We also found that the chronically treated HH patients showed significantly elevated oxidative stress levels despite therapeutic biochemical iron levels . In view of these observations, elevated oxidative stress may contribute to the increased ectopy of this patient group . Importantly, these patients showed normal left ventricular systolic function and did not fill the criteria for grade I or above left ventricular diastolic dysfunction, negating the influence of cardiac dysfunction caused by IO .…”
Section: Mechanismsmentioning
confidence: 60%
“…In human studies, interestingly, the association of elevated oxidative stress with atrial fibrillation has been documented in the postsurgical period . This is an interesting finding because atrial fibrillation is reported to be also associated with IO in humans as well, in which oxidative stress is also elevated …”
Section: Mechanismsmentioning
confidence: 82%
“…There are cases of cardiac arrest, syncope, and life-threatening ventricular arrhythmias that have been linked to hereditary hemochromatosis 13, 14. The mutation C282Y carried by the patient is the most commonly detected pathogenic alteration related to hemochromatosis in white populations and could have variable phenotypic expression and penetrance 13, 15. There are preliminary reports suggesting that this mutation could be associated with increased arrhythmic burden even in the absence of macroscopic iron deposition in the myocardium 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The mutation C282Y carried by the patient is the most commonly detected pathogenic alteration related to hemochromatosis in white populations and could have variable phenotypic expression and penetrance 13, 15. There are preliminary reports suggesting that this mutation could be associated with increased arrhythmic burden even in the absence of macroscopic iron deposition in the myocardium 15 . Although the ultimate diagnosis in this patient remains “idiopathic” VF with unknown causes, the exclusion of a role for the LMNA variant carries important implications in terms of cascade screening and calls for caution in the assessment of genetic variants in the absence of careful functional characterization.…”
Section: Discussionmentioning
confidence: 99%